Twenty years and twenty drawbacks of the Russian Constitution - Natalia A. Bobrova (Правоприменение, 2020)
The subject of the research is the legal norms of the current Constitution of the Russian Federation. The work analyzes the chapters of Constitution, identifies the main shortcomings of the existing norms that do not correspond to modern reality and puts forward proposals for their change.The purpose of the study is to confirm or disprove the hypothesis that changes to the Constitution of the Russian Federation are inevitable due to the presence of defects in it that cannot be eliminated in any other way.The methodological basis of the research is a set of general scientific methods of knowledge and special scientific techniques and methods developed in law, including: logical method, comparative legal analysis, system method and formal legal analysis.The main results and scope of their application. The problems that critically affect the stable development of our society and state and its success were formulated. Among these problems are: the absence in the Constitution of the institute of parliamentary control over the executive authorities; the rise of the institution of the President of the Russian Federation over the three branches of government; the unequal status of constituent entities of the Russian Federation; the absence in the Constitution of the concepts "public property" or "national heritage". A significant part of these problems is related to the text of the current Constitution of the Russian Federation. In this regard, the author notes that the current Constitution of the Russian Federation has many defects. The author points out 20 drawbacks of the current Constitution of Russia which make the authorities imitate the principles of democracy and people's power in the actual political practice and substantiates the conclusion on the necessity of the constitutional reform.Conclusions. Revision of the Constitution of the Russian Federation is inevitable , since the Basic Law of the country is not devoid of shortcomings that require correction and legislative changes.